2016
DOI: 10.1038/nmeth.3728
|View full text |Cite
|
Sign up to set email alerts
|

Parallel single-cell sequencing links transcriptional and epigenetic heterogeneity

Abstract: We report scM&T-seq, a method for parallel single-cell genome-wide methylome and transcriptome sequencing, allowing discovery of associations between transcriptional and epigenetic variation. Profiling of 61 mouse embryonic stem cells confirmed known links between DNA methylation and transcription. Notably, the method reveals novel associations between heterogeneously methylated distal regulatory elements and transcription of key pluripotency genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
603
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 633 publications
(619 citation statements)
references
References 28 publications
(56 reference statements)
15
603
0
1
Order By: Relevance
“…Several groups including those lead by Reik (Angermueller et al 2016;Clark et al 2016;Clark et al 2017), Vijg (Gravina et al 2015Gravina et al 2016;Yu et al 2017), Adey (Mulqueen et al 2017), and Eckardt (Luo et al 2017) have also demonstrated that methylation patterns can be generated from single cells. However, the principle caveat to these methods is that only a small amount of the genome is analyzed (often around 5%) and the same genomic regions are not analyzed in each cell, making cell-to-cell comparisons of specific loci difficult.…”
Section: Single Cell/cell-type Analysesmentioning
confidence: 99%
“…Several groups including those lead by Reik (Angermueller et al 2016;Clark et al 2016;Clark et al 2017), Vijg (Gravina et al 2015Gravina et al 2016;Yu et al 2017), Adey (Mulqueen et al 2017), and Eckardt (Luo et al 2017) have also demonstrated that methylation patterns can be generated from single cells. However, the principle caveat to these methods is that only a small amount of the genome is analyzed (often around 5%) and the same genomic regions are not analyzed in each cell, making cell-to-cell comparisons of specific loci difficult.…”
Section: Single Cell/cell-type Analysesmentioning
confidence: 99%
“…Although it is very difficult in general to measure multiple genomic quantities on the same single cell, one particular protocol (scM&T-seq) has been developed for measuring DNA methylation and gene expression in the same single cell [14]. It is possible that future protocols will enable other joint measurements.…”
Section: Overview Of Matchermentioning
confidence: 99%
“…Several high-throughput single cell versions of epigenetic assays have been developed, including single cell bisulfite sequencing (DNA methylation) [14], ATAC-seq (chromatin accessibility) [13], and ChIP-seq (histone modification) [12]. Each of the initial studies that pioneered these methods applied them to mouse embryonic stem cells (mESCs) grown in serum, a classic model system of stem cell biology.…”
Section: Data Description and Processingmentioning
confidence: 99%
See 2 more Smart Citations